Balance on the Brain: a randomised controlled trial evaluating the effect of a multimodal exercise programme on physical performance, falls, quality of life and cognition for people with mild cognitive impairment—study protocol. Issue 4 (18th April 2022) - Burton, Elissa; Hill, Keith; Ellis, Kathryn A; Hill, Anne-Marie; Lowry, Meggen; Moorin, Rachael; McVeigh, Joanne A; Jacques, Angela; Erickson, Kirk I; Tate, Joel; Bernard, Sarah; Orr, Carolyn F; et al.
Abstract : Introduction: Exercise and physical activity have been shown to improve cognition for people living with mild cognitive impairment (MCI). There is strong evidence for the benefits of aerobic exercise and medium evidence for participating in regular strength training for people with MCI. However, people living with MCI fall two times as often as those without cognitive impairment and the evidence is currently unknown as to whether balance training for people with MCI is beneficial, as has been demonstrated for older people without cognitive impairment. The aim of this study is to determine whether a balance-focused multimodal exercise intervention improves balance and reduces falls for people with MCI, compared with a control group receiving usual care. Methods and analysis: This single blind randomised controlled trial (Balance on the Brain) will be offered to 396 people with MCI living in the community. The multimodal exercise intervention consists of two balance programmes and a walking programme to be delivered by physiotherapists over a 6-month intervention period. All participants will be followed up over 12 months (for the intervention group, this involves 6-month intervention and 6-month maintenance). The primary outcomes are (1) balance performance and (2) rate of falls. Physical performance, levels of physical activity and sedentary behaviour, quality of life and cognition are secondary outcomes. A health economic analysis will be undertaken to evaluate the cost-effectiveness of the intervention compared with usual care. Ethics and dissemination: Ethics approval has been received from the South Metropolitan Health Service Human Research Ethics Committee (HREC), Curtin University HREC and the Western Australia Department of Health HREC; and approval has been received to obtain data for health costings from Services Australia. The results will be disseminated through peer-review publications, conference presentations and online platforms. Trial registration number: ACTRN12620001037998; Australian New Zealand Clinical Trials Registry (ANZCTR).